2016
DOI: 10.1098/rstb.2015.0348
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting BOLD: towards a dialogue between cognitive and cellular neuroscience

Abstract: Cognitive neuroscience depends on the use of blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) to probe brain function. Although commonly used as a surrogate measure of neuronal activity, BOLD signals actually reflect changes in brain blood oxygenation. Understanding the mechanisms linking neuronal activity to vascular perfusion is, therefore, critical in interpreting BOLD. Advances in cellular neuroscience demonstrating differences in this neurovascular relationship in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 148 publications
0
43
0
Order By: Relevance
“…To this effect, it has been shown that deconvolution produces improved estimation of effective connectivity [David et al, ; Ryali et al, ]. In fact, a recent paper presenting the viewpoint of cellular neuroscience on BOLD fMRI [Hall et al, ] discussed about several caveats in interpreting fMRI findings that deserve careful consideration based on the underlying cellular mechanisms. One such chief issue pertains to neurovascular dynamics or HRF variability, about which they say as follows: “advances in cellular neuroscience demonstrating differences in this neurovascular relationship in different brain regions, conditions or pathologies are often not accounted for when interpreting BOLD.” They suggest the use of computational modeling (e.g., deconvolution) to mitigate the issue.…”
Section: Methodsmentioning
confidence: 99%
“…To this effect, it has been shown that deconvolution produces improved estimation of effective connectivity [David et al, ; Ryali et al, ]. In fact, a recent paper presenting the viewpoint of cellular neuroscience on BOLD fMRI [Hall et al, ] discussed about several caveats in interpreting fMRI findings that deserve careful consideration based on the underlying cellular mechanisms. One such chief issue pertains to neurovascular dynamics or HRF variability, about which they say as follows: “advances in cellular neuroscience demonstrating differences in this neurovascular relationship in different brain regions, conditions or pathologies are often not accounted for when interpreting BOLD.” They suggest the use of computational modeling (e.g., deconvolution) to mitigate the issue.…”
Section: Methodsmentioning
confidence: 99%
“…It must be noted that all the entities in Eqns. (5)(6)(7)(8)(9) are absolute values. We varied the value of the off-diagonal elements of C (neural-FC) from 21 to 1 in steps of 0.25, to obtain the impact of HRF variability at different FC strengths.…”
Section: Dfc5mentioning
confidence: 99%
“…A recent article debating cellular neuroscience's viewpoints on BOLD fMRI presented numerous caveats while interpreting fMRI results, which demands careful consideration based on the underlying cellular mechanisms. They comment on neurovascular dynamics or HRF variability, which is one such issue, as follows: “advances in cellular neuroscience, demonstrating differences in this neurovascular relationship in different brain regions, conditions or pathologies are often not accounted for when interpreting BOLD.” They suggest the community use computational modeling (e.g., deconvolution) to mitigate the issue.…”
Section: Introductionmentioning
confidence: 99%
“…BOLD-fMRI reflects a spectrum of energy and blood-flow dependent processes (Logothetis et al, 2001) which are not fully understood (Logothetis, 2008, Hall et al, 2016). 1 H-MRS is a non-invasive measure of absolute concentrations of neurochemicals and, particularly in the absence of any sensory stimulation, has been exploited to identify biomarkers of normal and pathological brain states (Oz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%